(untitled) (مجلة البحوث الأكاديمية, 2026)
Background: Neurenteric cysts are rare congenital anomalies arising from abnormal separation of the embryonic notochord and foregut. Their association with midgut enteric duplication is exceptionally uncommon. Enteric duplication cysts (EDCs) themselves are rare developmental anomalies that may occur anywhere along the gastrointestinal tract, demonstrating wide variability in size, location, and symptoms. This study reports a rare case of a neurenteric cyst associated with midgut duplication in a Libyan patient and highlights its embryological background, diagnostic challenges, and surgical management. Methods: A comprehensive clinical, radiological, operative, and histopathological evaluation was performed. Diagnostic imaging included abdominal ultrasound and CT scan. Operative findings were documented, and histopathological analysis confirmed the nature of the lesion. A literature review was included to contextualize this unusual case. Results: Radiological imaging demonstrated a cystic abdominal lesion consistent with an enteric duplication structure. Intraoperative exploration confirmed a neurenteric cyst closely associated with duplicated midgut loops. Complete excision was performed without complications. Histology showed gastrointestinal-type mucosa and features characteristic of neurenteric cysts. The patient had an uneventful recovery and remained asymptomatic on follow-up. Conclusion: This case highlights the extreme rarity of neurenteric cysts associated with midgut duplication. Early recognition and surgical management are essential to avoid complications such as obstruction, infection, or perforation. This report contributes to the limited global and regional literature on complex EDC variants.